A neuropsychological-genetic profile of atypical cri du chat syndrome: implications for prognosis. Issue 7 (1st July 1999) - Cornish, K M; Cross, G; Green, A; Willatt, L; Bradshaw, J M
Abstract : Cri du chat syndrome is associated with a deletion on the short arm of chromosome 5. The main diagnostic feature is a high pitched, cat-like cry which has recently been localised to 5p15.3 and is separate from the remaining clinical features of the syndrome, which have been localised to 5p15.2. The present study describes a family of four who have a deletion slightly distal (5p15.3) to the critical region. Detailed neuropsychological evaluations indicated a similar pattern of cognitive performance to that reported for subjects with typical CDCS but with only minimal intellectual impairment. In addition, in this family the 5p deletion is transmitted in an autosomal dominant fashion, contrasting with most cases of CDCS, which are either de novo or occur as an unbalanced product of a balanced translocation in a normal parent. This study confirms the importance of differentiating between 5p deletions that coincide with the typical cri du chat phenotype which includes severe to profound learning disability and deletions that only delete the distal critical region that coincides with a milder degree of cognitive impairment and a much improved prognosis.